Investigating the course of L1 SASL development and L2 Afrikaans reading development in young deaf children following a newly introduced curriculum with SASL as both LoLT and school subject - Steyn, Minna A. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.